Peran Advokat dalam Pendampingan Hukum terhadap Klien untuk Menangani Kasus - Syahrial; Maya Intan Pratiwi; Rian Prayudi Saputra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rule of law is one of the principles of the Republic of Indonesia and is regulated in the 1945 Constitution. As the principle states that Equality Before The Law is a form of legal guarantee and provides certainty that everyone is equal before the law without any discrimination, besides that there is also the right to recognition and protection. Based on the principle and the right to protection, the Advocate profession is one of the professions that can be relied on. The role and function of an Advocate who is free, independent and responsible provides a glimmer of hope that the guarantee of certainty and justice will be fulfilled for people who really need legal assistance. The existence of Advocates also plays a role in the scope of justice which also has an important aspect, legal aid services from Advocates open up wide opportunities for the thirst for legal knowledge for the community. Therefore, as Officum Nobile or an honorable profession, Advocates must be truly reliable by the community.